Fetal growth restriction with abnormal individual biometric parameters at second trimester ultrasound is associated with small for gestational age neonate at delivery. (May 2022) - DeBolt, Chelsea A.; Sarker, Minhazur; Cohen, Natalie; Kaplowitz, Elianna; Buckley, Ayisha; Stone, Joanne; Bianco, Angela
Highlights: Compared 16–24 week growth restriction with normal biometry parameters to abnormal. Normal parameters had higher rates of resolved growth restriction prior to delivery. Normal parameters had lower rates of small for gestational age neonate at delivery. Abnormal parameters had higher rates of small for gestational age at delivery. Abnormal parameters had a trend toward increased NICU admission rate. Abstract: Objectives: To determine if early-onset fetal growth restriction with abnormal individual biometric parameters, defined as head circumference, abdominal circumference and femur length less than the 10th percentile, is associated with adverse neonatal outcomes compared to fetal growth restriction with normal biometric parameters. Study design: Retrospective cohort study including women diagnosed with fetal growth restriction between 16 and 24 weeks gestation who delivered a singleton, non-anomalous neonate at Mount Sinai Hospital from 2013 to 2019. The primary outcome was rate of small for gestational age neonate at delivery. Maternal, obstetric and neonatal outcomes were compared using multivariable regression analysis. Results: Patients diagnosed with fetal growth restriction with abnormal biometric parameters were more likely to be nulliparous, diagnosed with severe growth restriction and to receive antenatal corticosteroids than those with normal biometric parameters. The rate of small for gestational age neonate at delivery was higher in those with abnormal parameters (OR 4.0, 95% CI 1.7–9.2, p < 0.01) when compared to normal parameters. The rate of resolution of fetal growth restriction was higher in the normal biometric parameter group compared to those with abnormal parameters (OR 3.3, 95% CI 1.4–8.1, p < 0.01). Conclusions: Fetal growth restriction and normal biometric parameters diagnosed at second trimester ultrasound is associated with an increased likelihood of resolution of growth restriction and decreased likelihood of delivering a small for gestational age neonate.